Biochemistry of microbial itaconic acid production - Steiger, Matthias G.; Blumhoff, Marzena L.; Mattanovich, Diethard; Sauer, Michael (Frontiers in Microbiology, 2013)
Itaconic acid is an unsatured dicarbonic acid which has a high potential as a biochemical building block, because it can be used as a monomer for the production of a plethora of products including resins, plastics, paints and synthetic fibers. Some Aspergillus species, like A. itaconicus and A. terreus, show the ability to synthesize this organic acid and A. terreus can secrete significant amounts to the media (> 80 g/L). However, compared with the citric acid production process (titers > 200 g/L) the achieved titers are still low and the overall process is expensive because purified substrates are required for optimal productivity. Itaconate is formed by the enzymatic activity of a cis-aconitate decarboxylase (CadA) encoded by the cadA gene in A. terreus. Cloning of the cadA gene into the citric acid producing fungus A. niger showed that it is possible to produce itaconic acid also in a different host organism. This review will describe the current status and recent advances in the understanding of the molecular processes leading to the biotechnological production of itaconic acid.